Influence of leadership, motivation, cylinary and work environment to employee performance - Taufik, Mokhamad; Irdiana, Sukma (Wiga : Jurnal Penelitian Ilmu Ekonomi, 2017)
This study aims to determine the influence of leadership, motivation, discipline, and work environment significantly partially and simultaneously to the performance of subdistrict officials in Lumajang District. In this study used quantitative research methods using multiple linear regression analysis tools. Respondents were 78 subdistrict officials in Lumajang District. The results of this study are and documentation and continued with data processing to draw conclusions. From this research, it can be concluded that Leadership, motivation and work environment there is no significant partial positive effect on the performance of sub-district officials in Lumajang District. partially on the performance While the discipline there is a significant positive influence of subdistrict officials in Lumajang District. Simultaneously Leadership, motivation, discipline and work environment there is a significant positive influence partially on the performance of subdistrict officials in Lumajang District. The variables studied have an effect of 40.2% on employee performance, and the rest is influenced by other variables.